Bill Giles and Baseball. - Lord, John B. (Temple University Press, 2014)
Bill Giles oversaw one of the greatest eras of winning that the Philadelphia Phillies ever enjoyed. In Bill Giles and Baseball, John Lord chronicles Giles' remarkable career--which includes 44 years with the Phillies--to provide an insider's view of the business of the sport, which takes place off the field. Based on extensive interviews, Bill Giles and Baseball spans Giles' life from his childhood growing up in the game to the tumultuous years he spent as the president and managing partner of the Phillies. Purchasing the team in 1981.